2022
DOI: 10.3389/fgene.2022.866168
|View full text |Cite
|
Sign up to set email alerts
|

Developing a National Newborn Genomes Program: An Approach Driven by Ethics, Engagement and Co-design

Abstract: The transformative potential of whole genome sequencing (WGS) as a diagnostic tool in healthcare has been demonstrated by initiatives including the 100,000 Genomes Project and is now offered to certain patients in the National Health Service (NHS) in England. Building on these foundations, the utility of WGS in the newborn period can now be explored. Genomics England is working in partnership with NHS England and NHS Improvement and other healthcare, patient and public interest groups to design a research prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
(26 reference statements)
0
22
0
Order By: Relevance
“…Feasibility pilots over the last decade found that many of the initial ethical, legal, and social implications (ELSIs) of genomic NBS were not observed in practice. [23][24][25]46,[63][64][65] Many ELSIs are solved by adherence to the original criteria for NBS disorder selection and requiring informed parental consent. 31,46 Practical concerns, however, will be how to maintain the current 98% participation in NBS despite a requirement for consent and the allowable secondary use of genomic information.…”
Section: Methodologic Improvements Have Increasedmentioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility pilots over the last decade found that many of the initial ethical, legal, and social implications (ELSIs) of genomic NBS were not observed in practice. [23][24][25]46,[63][64][65] Many ELSIs are solved by adherence to the original criteria for NBS disorder selection and requiring informed parental consent. 31,46 Practical concerns, however, will be how to maintain the current 98% participation in NBS despite a requirement for consent and the allowable secondary use of genomic information.…”
Section: Methodologic Improvements Have Increasedmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20] rWGS is attractive for comprehensive NBS because it concomitantly examines almost all genetic diseases with similar time to result as biochemical NBS of DBSs by mass spectrometry (NBS-MS). [21][22][23][24][25] Here, we describe adaptation of Dx-rWGS methods for comprehensive NBS (NBS-rWGS). We detail scalable, feedbackinformed methods for newborn screening, diagnosis, and virtual, acute management guidance for 388 diseases with effective treatments and report analytic performance and clinical utility in large retrospective datasets.…”
Section: Introductionmentioning
confidence: 99%
“…For primary immunodeficiencies and DMD, genomic testing is required in NBS-positive subjects to define the specific genetic disorder, and, thereby, appropriate specific treatments. Secondly, there is now greater governmental attention to the unmet burden of childhood orphan genetic diseases, leading to large government funded NBS by genomic sequencing efforts in the United Kingdom, the European Union, and Qatar (Bick et al, 2022;Hopkins, Kinsella, & Evans, 2021;Mbarek et al, 2022;Pichini et al, 2022). Thirdly, there is now a large literature regarding the ELSI of NBS by genomic sequencing, as evidenced by an issue of the Hastings Center Report (Johnston et al, 2018).…”
mentioning
confidence: 99%
“…One of the places that may uncover answers to these and many other questions likely will be from a pilot National Newborn Genomes Program that Genomics England, in partnership with the National Health Service, is launching in 2023. 8 This study is uniquely positioned to address the effects of newborn genome sequencing on a national scale and includes research into aspects such as feasibility, consent procedures, use of data for research in future diagnostics and treatments and the long-term implications of storing and using a genome over an individual's lifetime. As genome sequencing is an extremely private dataset, there is a great need to handle these data correctly with room for stakeholders at the table during the design and pilot phase to ensure that such a programme is rolled out with the full trust and support of the public and with infrastructure and know-how in place.…”
mentioning
confidence: 99%
“…At its core is an alignment of expectations of participants and the public. One of the places that may uncover answers to these and many other questions likely will be from a pilot National Newborn Genomes Program that Genomics England, in partnership with the National Health Service, is launching in 2023 8 . This study is uniquely positioned to address the effects of newborn genome sequencing on a national scale and includes research into aspects such as feasibility, consent procedures, use of data for research in future diagnostics and treatments and the long‐term implications of storing and using a genome over an individual's lifetime.…”
mentioning
confidence: 99%